Thermal examination for the micropolar gold–blood nanofluid flow through a permeable channel subject to gyrotactic microorganisms - Khan, Arshad; Alyami, Maryam Ahmed; Alghamdi, Wajdi; Alqarni, M. M.; Yassen, Mansour F.; Tag Eldin, Elsayed (Frontiers in Energy Research, 2022)
Presently, the scientists across the world are carrying out the theoretical as well as the experimental examinations for describing the importance of nanofluid in the heat transfer phenomena. Such fluids can be obtained by suspending nanoparticles in base fluid. Experimentally, it has proved that the thermal characteristics of nanofluid are much better and appealing as compared to traditional fluid. The current work investigates the heat transfer for flow of blood that comprises of micropolar gold nanoparticles. The influence of chemically reactive activation energy, thermophoresis, thermal radiations and Brownian motion exists between the walls of channel. A microorganism creation also affects the concentration of nanoparticles inside the channel. Suitable transformation has used to change the mathematical model to dimensionless form and then have solved by employing the homotopy analysis method (HAM). In this investigation it has revealed that, fluid’s motion decays with growth in Reynolds, Darcy numbers and volumetric fraction. Thermal characteristics support by augmentation in volumetric fraction, thermophoresis, radiation and Brownian motion parameters while oppose by Prandtl number. Concentration of fluid grows up with augmentation in activation energy parameter and decays by growth in thermophoresis, Brownian motion, chemical reaction parameters and Schmidt number. Density of microorganism weakens by growth in Peclet and bioconvection Lewis numbers.